Long-period nutational-precessional motions of the instantaneous Earth rotation pole - V.Yu. Belashov; E.S. Belashova; O.A. Kharshiladze (Учёные записки Казанского университета: Серия Физико-математические науки, 2020)
The influence of the rotational regime on real long-period nutational-precessional motions of the instantaneous pole of the Earth’s rotation is considered. The solar magnetospheric (through changes in the angular velocity of rotation) mechanism of action is discussed. The observed 12-month oscillations of the instantaneous axis of rotation are explained by the influence of the deforming force arising when the angular velocity changes, which causes deformation of the figure that is not uniform in the longitudinal zones, without involving baric-circulation processes as an intermediate link. Thus, free (Chandler) and forced 12-month fluctuations of the pole position are considered from a single point of view, i.e., as resulting from the variability of the rotational regime of the Earth. The analysis of heliogeophysical data for 1900–2017 confirms the validity of the proposed relationship mechanism.